2004
DOI: 10.1159/000077730
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Lobe Hypoperfusion in Isolated Amnesia with Slow Onset: A Single Photon Emission Computer Tomography Study

Abstract: Single photon emission computer tomography (SPECT) applied early in the course of Alzheimer’s disease (AD) may identify regions with impaired brain function. Moreover, it may be relevant to characterize SPECT perfusion patterns in patients with mild cognitive impairment (MCI), in particular the subgroup of MCI patients with isolated amnesia, as these patients have been demonstrated to convert to AD in more than half of the cases within 3 years. The primary aim of the present study was to characterize the regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
3
10
0
Order By: Relevance
“…On the other hand, perfusion reduction in the posterior cingulate did not reach statistical significance. Posterior cingulate hypoperfusion has been frequently reported in series of MCI patients [18,20,21], but often hypoperfusion has been rather reported in the posterior parietal cortex and the precuneus [3,12,16,17]. Of note among SPECT studies, only those performed using 99m Tc-HMPAO [18,21] or 123 I-iodoamphetamine [20] disclosed posterior cingulate hypoperfusion, which has not, however, been reported by 99m Tc-ECD studies [3,12].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…On the other hand, perfusion reduction in the posterior cingulate did not reach statistical significance. Posterior cingulate hypoperfusion has been frequently reported in series of MCI patients [18,20,21], but often hypoperfusion has been rather reported in the posterior parietal cortex and the precuneus [3,12,16,17]. Of note among SPECT studies, only those performed using 99m Tc-HMPAO [18,21] or 123 I-iodoamphetamine [20] disclosed posterior cingulate hypoperfusion, which has not, however, been reported by 99m Tc-ECD studies [3,12].…”
Section: Discussionmentioning
confidence: 94%
“…The finding of hippocampal hypoperfusion raises the question about why hippocampal dysfunction has not been reported as an early marker of aMCI by a portion of the SPECT/PET literature [3,6,12,14,17,18,21], despite it being largely expected on the basis of current knowledge on the pathophysiology of AD. This issue has been discussed by a recent review [31], pointing to the problems of low spatial resolution of first-generation SPECT/PET equipment and to the smoothing procedure needed by the software programs performing voxelbased analysis (VBA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impairment of attention skills, apraxia, visuospatial dysfunction, and language problems are described early in the course of EOAD [4,5,6,7]. Studies on functional imaging in isolated slow progressing amnesia in the elderly have demonstrated that these patients may have a primary involvement of the temporal lobe [8], whereas the clinical profile of EOAD patients may reflect a primary involvement of the parietal region, which has also been suggested in both imaging studies and cerebrospinal fluid (CSF) studies of different EOAD presentations (posterior cortical atrophy and familial AD) [9,10]. Regarding clinical progression of the disease, several studies have demonstrated a faster progression [11,12,13,14] and a higher mortality [15] in EOAD patients compared to LOAD patients.…”
Section: Introductionmentioning
confidence: 99%
“…[48][49][50][51][52][53] More specifically, neuroimaging data indicate that one of the earliest preclinical markers of AD in people with MCI is the presence of brain hypoperfusion, specifically in brain regions destined to atrophy and die. [54][55][56][57][58][59][60][61][62][63][64][65] Atrophic changes in brain regions that initially show pathology typical of AD appear to follow brain hypoperfusion 6 not amyloid beta peptide accumulation as previously believed. 66 This conclusion is supported using perfusion and diffusion-weighted magnetic resonance imaging for evaluating tissue pathophysiology, which confirmed that microvascular perfusion impairment was the genesis of atrophy in AD.…”
mentioning
confidence: 99%